MODEL IMPLEMENTATION MIND MAPPING ON STUDENT LEARNING OUTCOMES IN CLASS IV SOCIAL STUDIES SUBJECTS AT SD NEGERI 23 LUBUKLINGGAU - Muhammad Juni Saputra; Yeni Asmara; Andri Valen (JURNAL EDUSCIENCE, 2023)
This study aims to determine the completeness of social studies learning outcomes for fourth grade students after applying the model Mind Mapping. The research method used in this research is quasi-experimental design research Pre-experiment One Group Pre-test and Post-test. The data collection technique was carried out using a test technique in the form of an essay with 5 questions. Data analysis techniques with steps: calculating the average, standard deviation, normality test and hypothesis testing. The population in this study were fourth grade students with a total sample of 22 students taken using a saturated sampling technique. The average score of student learning outcomes in the initial test was 40.31 and in the final test it was 86.41 and students with an average increase of 46.1. on datapost-test it was found that there were students who completed the standard of 65 out of the total class IV students with a learning completeness percentage of 100%. Based on the calculation results of the z-test analysis. known Z valuecount (8,63) WITHtable (1.64). Thus it can be concluded that after applying the modelMind Mapping in the social studies subject, the learning outcomes of fourth grade students at SD Negeri 23 Lubuklinggau are significantly complete.Keywords: Mind Mapping, Model, Social Studies Learning, Elementary SchoolAbstrakPenelitian ini bertujuan untuk mengetahui ketuntasan hasil belajar IPS siswa kelas IV setelah diterapkan model Mind Mapping. Jenis penelitian yang digunakan yaitu kuantitatif. Pengumpulan data dilakukan dengan teknik (pre-test dan post-test). Metode nya Pre-Experimental design. Instrument yang digunakan berbentuk soal essai. Populasi pada penelitian ini adalah siswa kelas IV dengan jumlah sampel sebanyak 22 siswa. Nilai rata-rata hasil belajar siswa pada tes awal sebesar 40,31 dan pada tes akhir menjadi 86,41 dan siswa dengan peningkatan rata-rata sebesar 46,1. Pada data post-test didapatkan ada siswa yang tuntas mencapai standar 65 dari total siswa kelas IV dengan persentase ketuntasan belajar sebesar 100%. Berdasarkan hasil hitung atau analisis uji-z. post-test dengan Zhitung (8,63) Ztabel (1,64), data post-test meningkat menjadi 100% atau semua siswa tuntas mencapai dari total siswa kelas IV yaitu 22 orang. Demikian,dapat disimpulkan bahwa setelah diterapkan model Mind Mapping pada mata pelajaran IPS siswa kelas IV secara signifikan tuntas.Kata Kunci: Mind Mapping, Model,Â  Pembelajaran IPS, Sekolah Dasar